Substituição da metionina pela betaína na dieta de Codornas de corte (coturnix coturnix coturnix) - Oliveira, Vanessa Raquel de Morais (2018)
Betaine is a derivative of the amino acid glycine, found in most organisms. Due to its function as a donor of methyl groups and low cost, has been used as a substitute for methionine in broilers nutrition. This study aimed to evaluate the effect of betaine supplementation in partial substitution of methionine + cystine requirement on productive performance, carcass yield and economic viability of betaine inclusion in the feed of European quails. A total of 920 European quails were used from 1 to 42 days of age. Birds were distributed in a completely randomized design of four treatments with 10 repetitions and 23 birds per experimental unit. Each treatment consisted of an experimental feed. In treatment 1, birds received a control feed, which was based in corn and soybean meal without any betaine supplementation and fulfilling nutritional requirements. In treatment 2, feed was formulated with a 5% reduction in methionine + cystine requirement values without betaine supplementation. In treatment 3, birds were fed with 5% reduction in methionine + cystine requirement values and supplemented with betaine. Treatment 4 consisted of a feed with 10% reduction in methionine + cystine requirement values with betaine supplementation. Analyses of variables revealed a significant effect (P<0.05) of treatments on weight gain of quails from 1 to 21 days of age, all treatments being superior to the control treatment. At 42 days of age, it was observed that all treatments were superior to the control treatment for slaughter weight and eviscerated weight. The weight of thigh + drumstick presented a satisfactory result in the treatments with betaine use, however, did not they differ from the treatment with 5% reduction of methionine + cystine without betaine supplementation. Treatments did not influence feed intake, weight gain and feed conversion in the period of 22 to 42 days of age. The treatments did not significantly influence (P> 0.05) the weight of lymphoid organs, liver and blood parameters of quails at 42 days of age. However, economic analysis of treatments demonstrated a reduction in price per kilogram of feed and better economic efficiency with betaine supplemented diets. Betaine can substitute up to 10% as methionine + cystine requirements of European quails, without compromising the productive performance, carcass characteristics, physical quality of the meat and the immune response of the birds